Sulfatide decreases the resistance to stress-induced apoptosis and increases P-selectin-mediated adhesion: a two-edged sword in breast cancer progression - Suchanski, Jaroslaw (Breast Cancer Res, 2018)
BACKGROUND: We have previously shown that galactosylceramide (GalCer) affects the tumourigenic and metastatic properties of breast cancer cells by acting as an anti-apoptotic molecule. Since GalCer is a precursor molecule in the synthesis of sulfatides, the present study was aimed to define the role of sulfatides in apoptosis and breast cancer progression. METHODS: Expression of GAL3ST1 in breast cancer cell lines and breast cancer tissue specimens was analysed using real-time PCR, western blotting and immunohistochemistry analysis. The amount of sulfatide, GalCer and ceramide was analysed by thin-layer chromatography binding assay and by the modified hydrophilic interaction liquid chromatography coupled with electrospray mass spectrometry methodology. The tumourigenicity of cancer cells was analysed by an in-vivo tumour growth assay. Apoptotic cells were detected based on caspase-3 activation and the TUNEL assay. The interaction of breast cancer cells with P-selectin or E-selectin was analysed using the flow adhesion assay. The ability of sulfatide-expressing cells to activate and aggregate platelets was studied using the flow-cytometry-based aggregation assay. RESULTS: Using two models of breast cancer, T47D cells with blocked synthesis of sulfatide and MDA-MB-231 cells with neosynthesis of this glycosphingolipid, we showed that high sulfatide levels resulted in increased sensitivity of cancer cells to apoptosis induced by hypoxia and doxorubicin in vitro, and decreased their tumourigenicity after transplantation into athymic nu/nu mice. Accordingly, a clinical study on GAL3ST1 expression in invasive ductal carcinoma revealed that its elevated level is associated with better prognosis. Using MDA-MB-231 cells with neosynthesis of sulfatide we also showed that sulfatide is responsible for adhesion of breast cancer cells to P-selectin-expressing cells, including platelets. Sulfatide also acted as an activating molecule, increasing the expression of P-selectin. CONCLUSIONS: This study demonstrates that increased synthesis of sulfatide sensitises cancer cells to microenvironmental stress factors such as hypoxia and anticancer drugs such as doxorubicin. However, sulfatide is probably not directly involved in apoptotic cascades, because its increased synthesis by GAL3ST1 decreased the amounts of its precursor, GalCer, a known anti-apoptotic molecule. On the other hand, our data support the view that sulfatides are malignancy-related adhesive molecules involved in activating and binding P-selectin-expressing platelets to breast cancer cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13058-018-1058-z) contains supplementary material, which is available to authorized users.